Fertility status of soils under different land uses in Chiephobozou sub-division of Kohima, Nagaland - DUTTA, MANOJ; KICHU, RIZONGBA; MEZHII, RUOPFIINUO; RAM, SEWAK (Journal of Soil and Water Conservation, 2020)
The effect of different land uses (orchard, shifting cultivation, lowland rice and forest) on soil fertility was studied in four villages namely, Tsiesema, Riisoma, Chiephobozou and Botsa falling under Chiephobozou sub-division of Kohima district. The soils were characterized by very strong to moderately acid (4.36 to 6.50) with high soil organic carbon content and medium to high levels of available N. Forest soils had higher cation exchange capacity, available N and P as compared to other land uses. The available K content in most of the land uses was low to medium.